Fucoidan/Polyvinylpyrrolidone/Hesperitin nanoparticle complex for corneal injury treatment: Synthesis, characterization, and therapeutic efficacy - Yalu Liu; Zhengpei Zhang; Lina Guan; Jie Li; Xing Ge; Xiaochen Wu; Haiyang Liu (International Journal of Pharmaceutics: X)
Corneal injury is a common ailment that, if not addressed promptly and efficiently, has the potential to result in significant visual impairment. This study investigates the therapeutic potential of a novel FU/PVP/Hes nanoparticle complex composed of fucoidan (FU), polyvinylpyrrolidone (PVP), and hesperitin (Hes) for corneal injury treatment. The FU/PVP/Hes nanoparticles were synthesized using a solvent evaporation method and characterized for their morphology, size distribution, biocompatibility, antioxidant activity, and anti-inflammatory capacity. The nanoparticles demonstrated excellent biocompatibility with low hemolysis rates and minimal cytotoxicity. They also exhibited potent antioxidant and anti-inflammatory properties, which were attributed to the enhanced solubility and bioavailability of Hes through nanoparticle formation. In vivo investigations employing a mouse model of corneal injury induced by alkali burns showed that the FU/PVP/Hes nanoparticles significantly promoted corneal epithelial healing, reduced corneal opacity, and suppressed the elevation of inflammatory cytokines. Histopathological analysis confirmed the nanoparticles' ability to facilitate corneal tissue repair. The study concludes that the FU/PVP/Hes nanoparticle complex is a promising therapeutic agent for corneal injury treatment due to its biocompatibility and multifaceted therapeutic effects.